Full-scale self-propulsion simulation with a discretized propeller - Zhang Qingshan (Krylov State Research Centre, 2021)
A comparison between towing tank testing and full-scale CFD simulations is presented at three different target speeds. For the current self-propulsion simulation, the self-propulsion point was obtained using polynomial interpolation. The studies of boundary layer thickness, a basic grid uncertainty assessment and verification were performed to give some confidence of grid application to current self-propulsion simulation. All simulations are performed using a commercial CFD software STAR-CCM+. It is concluded that with high-fidelity numerical methods, it’s possible to treat hull roughness and directly calculate full-scale flow characteristics, including the effects of the free surface, none-linearity, turbulence and the interaction between propeller, hull and the flow field.